If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = -2x + 3 Reorder the terms: -2 + 4x = -2x + 3 Reorder the terms: -2 + 4x = 3 + -2x Solving -2 + 4x = 3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -2 + 4x + 2x = 3 + -2x + 2x Combine like terms: 4x + 2x = 6x -2 + 6x = 3 + -2x + 2x Combine like terms: -2x + 2x = 0 -2 + 6x = 3 + 0 -2 + 6x = 3 Add '2' to each side of the equation. -2 + 2 + 6x = 3 + 2 Combine like terms: -2 + 2 = 0 0 + 6x = 3 + 2 6x = 3 + 2 Combine like terms: 3 + 2 = 5 6x = 5 Divide each side by '6'. x = 0.8333333333 Simplifying x = 0.8333333333
| 8.83=x+3.51 | | 6xy+3x-2=9y+2 | | 6y-9-2y+4=0 | | 3+2j=7 | | 3xy-14=12z | | 3n-7=6 | | 10x+2+68+70=180 | | x-10.16=-12 | | -8y-4=2y+16 | | 8x-5x-11=52 | | 5(x+1)-4x=6-2x-(4-2x) | | (x+5)(x-8)(4x-5)=0 | | x+4.8=-7.7 | | 5z=7y+2xy-3 | | 3u-4=5 | | R-2+R+7= | | -28+x=2.6 | | 8y+11=12y+7x | | -3=18m+6n | | 1x+11+2x-5=90 | | sqrt(7x-7)-9=3x-20 | | 43.01*0.84= | | -345=-7(7-6n)-5n | | s(t)=16t^2+4t+7 | | x+87+50+50=180 | | 10m+50=7m+80 | | 3-(x+2)=7 | | 43.4-0.39*0.84= | | (d^4+3d^3-6d^2-28D)y=0 | | y=10-5*-2 | | (-3x)+y=0 | | s(t)=-16t^2+4t+7 |